2019
DOI: 10.1002/adsc.201900540
|View full text |Cite
|
Sign up to set email alerts
|

A Drastic Effect of TEMPO in Zinc‐Catalyzed Stannylation of Terminal Alkynes with Hydrostannanes via Dehydrogenation and Oxidative Dehydrogenation

Abstract: With a system consisting of a catalytic zinc Lewis acid, pyridine, and TEMPO in a nitrile medium, terminal alkynes coupled with HSnBu 3 , providing alkynylstannanes with structural diversity. The resulting alkynylstannane, without being isolated, could be directly used for Pd-and Cu-catalyzed transformations to deliver internal alkynes and more intricate tin-atom-containing molecules. Mechanistic studies indicated that TEMPOSnBu 3 formed in situ from TEMPO and HSnBu 3 works to stannylate the terminal alkyne in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 81 publications
1
11
0
Order By: Relevance
“…After nucleophilic addition to tributyltin fluoride ( 10-236 ), the corresponding products could be produced. Recently, Tsuchimoto et al combined this Cu-catalyzed alkynylstannylation protocol with a Zn-catalyzed stannylation of terminal alkynes . In 2019, Yoshida et al revealed a Cu-catalyzed arylstannylation of arynes with electron-deficient arylstannanes 10-238 (Scheme b) .…”
Section: Transition-metal-catalyzed Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…After nucleophilic addition to tributyltin fluoride ( 10-236 ), the corresponding products could be produced. Recently, Tsuchimoto et al combined this Cu-catalyzed alkynylstannylation protocol with a Zn-catalyzed stannylation of terminal alkynes . In 2019, Yoshida et al revealed a Cu-catalyzed arylstannylation of arynes with electron-deficient arylstannanes 10-238 (Scheme b) .…”
Section: Transition-metal-catalyzed Reactionsmentioning
confidence: 99%
“…Recently, Tsuchimoto et al combined this Cu-catalyzed alkynylstannylation protocol with a Zn-catalyzed stannylation of terminal alkynes. 857 In 2019, Yoshida et al revealed a Cu-catalyzed arylstannylation of arynes with electron-deficient arylstannanes 10-238 (Scheme 259b). 858 By using copper(I) 2-thiophenecarboxylate (CuTC) as the catalyst, both substituted ortho-stannylbiaryls 10-240 and teraryls 10-241 could be prepared, the mechanistic pathway of which involves either a single or double insertion of arynes into arylstannanes, respectively.…”
Section: Copper-catalyzed/mediated Reactionsmentioning
confidence: 99%
“…2 Thus, the Zn (II) ion, being economically viable, naturally available in abundance, and biocompatible, plays a substantial role in synthetic chemistry. [3][4][5][6] Unlike transition metals, zinc-catalyzed reactions are mechanistically distinct for specific reactions such as polymerization, [7][8][9] oxidative coupling reactions, [10][11][12] and dehydrocoupling of alcohols with silanes. [13][14][15] From the synthesis of the first organozinc compound-diethylzinc-from metallic zinc and ethyl iodide by Frankland et al to date, several potential applications of organo-zinc compounds have been reported, demonstrating the evolution of synthetic organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Stannylation of terminal alkynes with Bu 3 SnH using TEMPO and a Zn catalyst was presented (Scheme b). Reactions proceed via formation of TEMPOSnBu 3 , which transfers the stannyl group to the alkyne through zinc catalysis …”
Section: Oxidation Reactionsmentioning
confidence: 99%